Demystifying Balint culture and its impact: An autoethnographic analysis. (January 2018) - Sternlieb, Jeffrey L
Balint groups are a structured group process designed for physicians and other helping professionals to provide feedback to each other concerning troublesome patient encounters. The process of Balint groups has survived and even thrived for more than a half century since their inception, suggesting their inherent value. However, measuring the impact in order to communicate the nature of that value has been elusive. A recent literature review highlighted the equivocal nature of research results and suggested that well-designed qualitative research may be more effective in selecting target measures which could result in better evidence for this group process. This paper describes such an effort using a qualitative analysis of the author's own reflections about significant moments and learnings while participating in Balint groups.